2010
DOI: 10.1523/jneurosci.1938-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Why Variability Facilitates Spinal Learning

Abstract: Spinal Wistar Hannover rats trained to step bipedally on a treadmill with manual assistance of the hindlimbs have been shown to improve their stepping ability. Given the improvement in motor performance with practice and the ability of the spinal cord circuitry to learn to step more effectively when the mode of training allows variability, we examined why this intrinsic variability is an important factor. Intramuscular EMG electrodes were implanted to monitor and compare the patterns of activation of flexor (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 34 publications
4
60
0
1
Order By: Relevance
“…There is increasing evidence that providing more variable practice conditions during training enhances motor performance [56,[61][62][63]. This is also implied from clinical research showing that overground gait training or therapist-assisted BWSTT enables better ambulatory outcomes in people with SCI or stroke than with robotguided training [16,61].…”
Section: Movement Variability During Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence that providing more variable practice conditions during training enhances motor performance [56,[61][62][63]. This is also implied from clinical research showing that overground gait training or therapist-assisted BWSTT enables better ambulatory outcomes in people with SCI or stroke than with robotguided training [16,61].…”
Section: Movement Variability During Trainingmentioning
confidence: 99%
“…This is also implied from clinical research showing that overground gait training or therapist-assisted BWSTT enables better ambulatory outcomes in people with SCI or stroke than with robotguided training [16,61]. The rigid imposition of movement trajectories by robot-assisted training limits the variability with which the lower limbs are moved and consequently could interfere with the nervous system's ability to effectively relearn gait patterns [61][62]. Indeed, variability during practice is seen as a key feature for facilitating learning because the nervous system is presented with repeated (and varied) opportunities to experience errors and solve motor problems [55], as opposed to simply learning how to reproduce an imposed trajectory [63].…”
Section: Movement Variability During Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…These new controllers allow active participation of patients in the kinematics of locomotion, which may be more effective for motor learning [26][27]. However, the effects on the cardiorespiratory system have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, effective practice requires more than just movement repetitions. Animal studies have shown that training with a variable stepping pattern results in higher levels of recovery than walking with a fixed stepping pattren [128,129]. Although recovery mechanisms in mice and rats may not be representative for humans, similar benefits of movement variability are seen in neurological patients, suggesting that training with kinematic variability is advantageous.…”
Section: Movement Variabilitymentioning
confidence: 99%